The Influence of Financial Effectiveness and Financial Literacy on the Financial Behavior of Generation Z in Mukomuko Regency, Bengkulu Province - Japriani, Meli; Marlina, Lilis; Suprianto, Iwil (Journal of Advances in Accounting, Economics, and Management, 2023)
This study aims to analyze the effect of financial effectiveness and financial literacy on individual financial behavior. The method used is quantitative with a survey approach using a questionnaire as a data collection instrument. The research sample consisted of 60 respondents selected by cluster sampling. Data were analyzed using SmartPLS 4.0 software. The results of the study indicate that financial effectiveness and financial literacy have a positive and significant effect on financial behavior. These findings indicate that an individual's ability to manage finances effectively and the level of understanding of financial concepts play an important role in forming adaptive and responsible financial behavior. The implications of this study emphasize the importance of increasing literacy and effectiveness of financial management to encourage more rational and planned financial decision-making. This study contributes to the development of financial education strategies, especially for generation Z in achieving long-term financial well-being.